Analisis Konsepsi Guru-Guru Matematika Sekolah Menengah Tentang Hakikat Masalah Matematika dalam Pendekatan Students Centered Learning (Studi Kasus dalam Pembelajaran Matematika di SMA Kota Palembang) - Scristia; Hiltrimartin, Cecil; Santoso, Budi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2018)
This study is a case study to examine, make interpretations and gain a deep understanding of the conception and the use of mathematical problems in the SCL approach applied in the classroom. This study aims to explore the understanding of high school mathematics teachers in Palembang city of the nature of a problem in the SCL approach. This study uses questionnaires, observations and documents as the main data and interviews as supporting data. This study takes a sample of 3 high school teachers in Palembang City.